Educational Marketing Management In Increasing The Competitiveness Of Institutions - Yulianto, Edi (CV. Inara, 2024)
This research is motivated by the phenomenon of Islamic educational institutions increasing their competitiveness, so that they are able to compete with general educational institutions in the world of education. Marketing management is an important and strategic factor in increasing the competitiveness of institutions. Based on the Higher Education Entrance Test Institute, it is Islamic educational institutions that are ranked first as institutions with the highest scores and are accepted in universities both domestically and abroad. Apart from that, the public's critical power regarding assessments of Islamic educational institutions greatly influences the quality of the institution. The research focus in writing this dissertation is on the management and marketing programs of educational institutions in increasing competitiveness. The aim of this research is to find and formulate propositions for education market segmentation, positioning, funding and educational products at Madrasah Aliyah Negeri 2 Malang City and Madrasah Aliyah Negeri 2 Kediri City. Based on the results of this research, the researcher concluded that: (1) Market segmentation divides student groups based on intellectual level, then these educational groups want to study academic or non-academic education, develop their skills or academic qualifications, market segmentation can analyze more deeply the prospective students who register In this case, it is seen from the needs, understanding, preferences and challenges faced by students. (2) The positioning carried out is to maximize the educational institution's superior and non-leading programs and then maintain relationships with alumni in order to obtain more information and a good reputation and image of the educational institution (3) The institution's marketing funding looks at and understands the factors in its financing starting from starting from marketing objectives, market evaluation, target audience, marketing mix, determining the budget, providing monitoring and carrying out evaluations, of course this is flexible. (4) Marketing products of educational institutions, namely maintaining the performance of their superior programs so that they increase. The superior products owned by these institutions are an important factor in encouraging the development of educational institutions and can increase the competitiveness of educational institutions.